A review of Labidostomis species similar to L. longimana from southeastern Europe with descriptions of two new species from Greece and Turkey (Coleoptera: Chrysomelidae: Cryptocephalinae: Clytrini) - Bezděk, Jan; Regalin, Renato (Zootaxa, 2017)
This publication reviews the Labidostomis species from Southeastern Europe similar to L. longimana. Two new species, L. daccordii sp. nov. (Central Greece) and L. leonardii (Greece: Kos Island, Turkey), are described. The type specimens of L. balcanica Tomov, 1987 (Croatia), L. graeca Tomov, 1990 and L. tymphristica Tomov, 1990 (both from Greece) were studied, all three species are confirmed as valid and their diagnostic characters are described. The aedeagus sclerites are introduced as useful character to separate Labidostomis species.